A comparative study of the application-based properties of hot melt adhesives (HMAs) formulated with different waxes. (December 2021) - Robertson, Divann; van Reenen, Albert; Duveskog, Heidi; Brady, Fran
Abstract: In this study, three chemically similar but morphologically different high melting hydrocarbon waxes having similar DSC peak melting temperatures were analysed, and the influence of their molecular architectures on hot melt adhesive (HMA) performance, was evaluated. Selected waxes included each of the following types: Fischer Tropsch wax (FT), by-product polyethylene wax (BPPE) and first intention polyethylene wax (FIPE). Both, ethylene-co-vinyl acetate (EVA) and metallocene catalysed polyethylene (mPE) based HMAs were formulated. The high chain linearity of FT wax resulted in faster crystallization and faster adhesive set times as well as higher peel adhesion, shear adhesion and IOPP heat resistance temperatures. Wax viscosities were in direct correlation with resultant HMA viscosities. EVA HMAs had longer set times and were more prone to thermal degradation upon prolonged exposure to elevated temperatures and was most pronounced for FIPE wax. Average traction force was dependent on the open time and wax/polymer combination with FT showing a smaller open time window for both EVA and mPE based HMAs.